Pengenalan Proses Produksi dan Pemanfaatan Herbal Kering Berkhasiat Obat pada Koperasi Perempuan Pelestari Hutan - Yuwana; Syafnil; Fatharani, Arina (DHARMA RAFLESIA, 2023)
The target audience of community service activities was the Forest Conservation Women's Cooperative (KPPH), domiciled in Teladan Village, Curup District, Rejang Lebong Regency, Bengkulu Province, which manages a forest area with potential plants that could be cultivated and processed into herbal plants. One of them is pulutan leaves (Urena lobata L.) which have medicinal properties that residents in treating various diseases have used. These leaves have the potential to be dried herbs by transfer of Appropriate Technology (TTG) by introducing the process of pulutan leaves drying into dried herbs. The drying process was carried out using a dual heat collector solar energy dryer developed by the Department of Agricultural Technology. The process was analyzed to determine the drying time of pulutan leaves into dried herbs. For the next step, the leaves are packed to be stored. The process and utilization of pulutan leaves into dried herbs using a solar energy hybrid dryer required 8 hours and it was faster than the drying time in the open sun. The community service activities have been carried out well and successfully and provided benefits to the target audience.